Intraoperative photodynamic therapy in patients with IIIb and IIIc stages of locally advanced breast cancer - D. D. Pak; Е. V. Filonenko; E. К. Saribekyan (Biomedical Photonics)
The study of efficiency of intraoperative photodynamic therapy (PDT) with Photosens as the step of combined modality treatment in patients with IIIВ and IIIС stages of breast cancer was performed. The long-term outcomes were evaluated in two groups of patients: group 1 – after radical extended mastectomy combined with chemotherapy, radiotherapy and chemo- and hormonal therapy (138 patients), group 2 – the same treatment combined with intraoperative PDT (36 patients). For the patients with PDT photosens was administered i.v. in single dose 0.3 mg/kg for 2 h before surgery. The irradiation of operative field was performed single time (the light dose 30 J/cm2), with separate irradiation of subclavian, axillar and adjacent regions (the light dose 50 J/cm2). The results showed that intraoperative PDT was associated with better recurrence-free survival rates in patients with breast cancer: in the PDT group the average recurrence free survival was 44.9±3.4 months, in the group without PDT — 35.3±2.1 months. The obtained results confirm that intraoperative PDT for locally advanced breast cancer can be used successfully for devitalization of cancer cells on the wound superface and for prevention of intraoperative tumor dissemination and post-operative recurrence.